Waqf land in Malaysia: Legal and non-legal impediments with propositions / Siti Khadijah Abdullah Sanek...[et al.] - Abdullah Sanek, Siti Khadijah; Erlen Joni, Ekmil Krisnawati; Ismail, Siti Nurbaya (Universiti Teknologi MARA, Kedah, 2017)
In Malaysia, any waqf related matter is subjected to different Islamic Religious Council of each state causing many hindrances in its management and implementation. As such, this paper seeks to identify legal and non-legal impediments encountered in the management of waqf land in Malaysia. A few propositions are discussed about legal and non-legal aspect where the discussion on non-legal aspect will be scrutinized by proposing a web based Geographical Information System (GIS) model. The usage of web based applications is preferred than the manual system due to its data storage capability on the servers which could ease the record keeping process. Additionally, spatial databases are a prerequisite element for any GIS program to ensure all the required data to be fully functioning such as GIS map which may be able to display all data layers and dimensions. The study indicates that this integration could ensure that waqf land data management would become more systematic and accurate.